On Some Fixed Point Results in LP Space - E.Eljaneid, Nedal Hassan (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2017)
The Banach fixed point theorem or contraction theorem of a complete metric space into itself .It state conditions sufficient for the existence and uniqueness of a fixed point.